Legal Reconstruction of Mediation in Village Conflict Resolution Based on Dignified Justice - Wartoyo, Franciscus Xaverius; Triwijanarko, Dinda (Unissula, 2025)
As the smallest unit in the Indonesian government system, villages play a crucial role in maintaining social harmony and resolving conflicts within communities. Village heads and their staff, such as neighborhood heads and hamlet heads, have legal and moral responsibilities as extensions of the local government. Based on Law Number 6 of 2014 and its most recent amendment, Number 3 of 2024, village heads are obligated to resolve disputes within village communities. This study aims to analyze the role of village heads and village community institutions in conflict resolution through customary law and non-litigation approaches. This study used qualitative methods, focusing on analyzing the role of village heads and community institutions in conflict resolution through customary law and non-litigation approaches. Furthermore, this study highlights the harmonization of Pancasila values in pluralistic village communities and identifies challenges and solutions in implementing the latest regulations at the village level. The results indicate that empowering village heads through mediator training and legal support can increase the effectiveness of peaceful and just resolutions. In conclusion, harmonizing Pancasila values and integrating customary law into village conflict resolution mechanisms is crucial for maintaining the unity and well-being of village communities.